Effect of NaCI solution concentration, particle size and ratio on viscosity inhibitor of porang flour - Mohammad Amirul Muzakki; Erliza Noor; Anto Tri Sugiarto (AGROINTEK, 2025)
Porang flour has a fairly high glucomannan content, up to 65%, which can accelerate the formation or viscosity process in porang flour. The high viscosities cannot be applied to rotating flow nozzle-type hydrodynamic cavitation devices designed to form cavitation bubbles during degradation. In this study, the preeminent process parameters will be sought, especially for particle size, concentration of NaCl solution, and the ratio (porang flour : NaCl solution: isopropyl alcohol) to the inhibition of viscosity formation at porang flour. It aims to analyze those factors effect on viscosity inhibition to support the performance of cavitation bubble formation during the process of breaking cell walls in porang flour. This process was carried out in a factorial complete randomized design (CRD) on all 3 factors with 2 repetitions. The results show that the factor of particle size, the concentration of NaCl, and the ratio significantly affected the decrease in the viscosity of porang flour. Large particle sizes with high concentrations of NaCl can reduce the viscosity level up to 10 cP. The results of the addition of isopropyl alcohol in the ratio (mesh size 40: 5% NaCl: isopropyl alcohol) at a concentration of 2.5% can produce a viscosity of up to 10 cP with a gel level in the sample that is more invisible and not concentrated. In the experimental stage using the swirling flow nozzle type hydrodynamic cavitation technique with the selected formulation, it was seen that the calcium oxalate diminution in porang flour was up to 97.2 mg/100g with a degradation percentage of 52.63%. The residual calcium oxalate in porang flour contradicted the standard for human body tolerance, explicitly 71 mg/100g. Therefore, the resultant flour is not safe to consume. Furthermore, the yield of calcium oxalate at this experimental stage still does not meet SNI 7938:2020, that is, 30 g/100g.